MANIFESTASI DISFUNGSI BEBERAPA HORMON DARI SEORANG PENDERITA DENGAN RIWAYAT ADENOMA HIPOFISIS - Haryant, Elizabet; Gotera, Wira (journal of internal medicine, 2007)
The sellar region is a site of various types of tumors. Pituitary adenomas are common neoplasms of the anterior pituitarygland. They arise from epithelial pituitary cells and account for 10-15% of all intracranial tumor. The remaining one-third ofpituitary adenomas is endocrinologically silent, known as nonfunctioning pituitary adenomas, and cause symptoms or signs dueto tumor growth. Incidence of pituitary adenomas is difficult to know with certainty because they are often asymptomatic;autopsy estimates range from 2.7 to 27%. There is not a predominance in either men or women. An increasing proportion ofpituitary adenomas are recognized in the elderly, raising the question of their optimal diagnosis and management. However, theadvent of the sophistical imaging systems for the brain such as the CT and MRI scans have greatly contributed to the earlydetection of these tumors. This is our reported case the occurrence of many endocrinology disorders with a pituitary adenoma. A79 year old male with a known pituitary macroadenoma, who presented with a chief complaint shortness of breath and took adouble dose of costison a view days ago. The related symptom also decreased libido and progressive impotence, mild coldintolerance and decreased appetite. Physical exam was notable for a BP of 180/115, pulse of 120 (with significant orthostaticchanges), pallor, bilateral gynecomastia He also complained of generalized fatigue and weakness. He had history at 1988 withCVA and got euthyrox for the hypotiroidsm. In 1998 was hospitalized on Danderyds Hospital with diagnosed adenoma pituitaryfrom the CT-Scan, and got trombyl 180 mg 2 x 1 tablet, triatec 4 x 5 mg, omeprazole 4 x 20 mg, duroferon 4 x 100 mg, and alsonibido 4 ml every 4 month. On 2005 he developed a severe and sudden headache, disorientation, weakness and fever. Thelaboratory result were testosteron 15 mmol/L (10-30 mmol/L), prolaktin 17 µg/L (normal 3-13 µg/L), tyrotrhopin TSH (thyroidstimulating hormone) 0,15 mE/L (normal 0.4-3.5 mE/L), S-IGF-I 57 µ/L (normal 85-220 µ/L) TSH 0,075 mE/L (normal 0.4-3.3mE/L), FT4 9 pmol/L (normal 8-16 pmol/L), kortisol 98 nmol/L (normal, 08.00 am; 200-700 nmol/L, 10.00 pm; 50-200 nmol/L),the echocardiografi was EF(ejection fraction) 35-40%, angiografi with striktur on proximal LAD. For the second CT-scan wasfounded the increasing size of the adenoma pituitary 3 x 4 centimeter. Because of the presence and the past history also supportingwith another laboratory and rontgen examination. The diagnosis of a clinically nonfunctioning pituitary adenoma with hypogonadismtipe was made, but now with conditions acute heart failure, pleural effusion and bronchopneumonia. Nonfunctional pituitaryadenomas, also called null-cell adenomas, are the most common macroadenomas (> 1 cm). Nonfunctional adenomas usuallypresent with local mass effects (e.g., optic chiasm compression), neurologic symptoms (cranial nerve III, IV and VI palsies) andpituitary hormone deficiencies (e.g., hypogonadism). Headache, nausea, vomiting, ophthalmoplegia and reduced level ofconsciousness, can occur in patients with large pituitary adenomas who suddenly deteriorate clinically. Pituitary apoplexy, a lifethreateningsudden hemorrhage or infarction of a pituitary adenoma characterized by severe. The majority of patients with pituitary adenomas present with signs and symptoms reflecting excess hormone production. This case illustrates one of the many type frompituitary adenoma and also the another conditions that can addition severity of the disease. The professional clinical examinationshould be done for decreasing the mortality